Lecturers’ Commitment And Students’ Academic Achievement: Case Study From Existing Teaching Evaluation Result (TER) - Tengku Noorainun Tengku Shahdan; Muhammad Faizal A. Ghani; Faisol Elham (Intelektual Pustaka Media Utama, 2012)
This study reported herein is the used of TER as the basis to ascertain if the commitment of the lecturers can lead to academic excellence of the students. The TER is comprised of questionnaires in which the foundation students are the respondents (N=433) in assessing the courses as well as the lecturers. The performances of the students in the form of final exam grades are also used. The respondents were comprised of 85% Indian, 10% Malay and 5% Chinese. There are more than 30% of the students who have obtained a grade of A- and better, the TER was less than 80%. Due to the limitation and the unavailability of matching each student to their evaluation towards the lecturers, the results presented above is weakly conclusive. It is recommended that future research in similar areas to incorporate the matching of students be made with the lecturers to obtain reliable and conclusive result.